Dielectric Constant Determination using Dual Doppler Modules - Prapan Leekul; Bonny Mgawe; Twahir Kazema; Hoang Nam Dao; Phaophak Sirisuk; Monai Krairiksh (My University, 2021)
This paper presents a dielectric constant determination system based on dual Doppler modules. The key principle is to assign two slightly different radio frequencies to each module. It is demonstrated that dielectric constant of a material under test can be determined from the measured reflection coefficient. The concept was validated at 10 GHz band by measuring reflected waves from various materials including soil with different moisture content. Results illustrated good agreement between measured results from the proposed sensor as compared with the literatures. The results confirm that the proposed technique is applicable for monitoring soil characteristics.
Keywords: Soil Moisture and Remote Sensing; Microwave and Dielectric Measurement Techniques; Geophysical Methods and Applications